Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Dayamega Pratama Medan - Aisyah Harahap; Waizul Qarni (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The purpose of this study is to analyze the influence of work environment and job stress on employee performance at PT. Dayamega Pratama Medan. This research employs a quantitative approach, where data is collected through questionnaire method. Data processing is conducted using SPSS 23 for Windows. The population used in this study consists of 52 employees of PT. Dayamega Pratama Medan, all of whom are selected as samples. The data analysis technique employed includes descriptive analysis and multiple linear regression analysis with a significance level of 5%. Based on the F-test results, an F-calculated value of 22.940 was obtained, which is greater than the F-table value of 3.19, indicating that the independent variables of work environment and job stress simultaneously have a significant influence on employee performance. The partial t-test results show that work environment does not provide a significant influence on employee performance, as indicated by a significance value of 0.206 (> 0.05) and a t-calculated value of -1.281 (< t-table 1.674). Conversely, job stress is proven to have a positive and significant influence on employee performance, as demonstrated by a significance value of 0.000 (< 0.05) and a t-calculated value of 6.756 (> t-table 1.674). This indicates that job stress is the main factor influencing employee performance. Based on the correlation coefficient test (R), the relationship between work environment, job stress, and employee performance is considered strong. Nevertheless, job stress emerges as the most dominant variable influencing employee performance at PT. Dayamega Pratama Medan. Therefore, effective job stress management is expected to contribute to improved employee performance, while high levels of job stress have the potential to reduce performance.